The Promise of Whole Genome Pathogen Sequencing for the Molecular Epidemiology of Emerging Aquaculture Pathogens - Bayliss, Sion C.; Verner-Jeffreys, David W.; Bartie, Kerry L.; Aanensen, David M.; Sheppard, Samuel K.; Adams, Alexandra; Feil, Edward J. (Frontiers in Microbiology, 2017)
Aquaculture is the fastest growing food-producing sector, and the sustainability of this industry is critical both for global food security and economic welfare. The management of infectious disease represents a key challenge. Here we discuss the opportunities afforded by whole genome sequencing of bacterial and viral pathogens of aquaculture to mitigate disease emergence and spread. We outline, by way of comparison, how sequencing technology is transforming the molecular epidemiology of pathogens of public health importance, emphasising the importance of community-oriented databases and analysis tools.